"Laser dentistry"-The need of the hour: A cross-sectional study - Aparnna Dhayanidhi; Narmatha Mudiarasu; Abirami Mathivanan; Janani Rajeswari Gopalkrishnan; Saranya Kulandaivelu Kasinathan Nagarajan; Khaniya Bharathan (Wolters Kluwer Medknow Publications, 2020)
Aim: The increase in the technological development in dentistry has led to a better and efficient treatment being rendered to the patient. One such development is the application of laser in the field of dentistry. The introduction of laser has provided various advantages to the dentist. Therefore, a study was conducted to assess awareness among the dentists in Coimbatore district about the application of laser. Materials and Methods: A cross-sectional study was conducted among the dentists in Coimbatore district. A questionnaire consisting of three parts was used to assess the knowledge, attitude, and practice of laser dentistry. Results: The results were tabulated, and the percentages were statistically analyzed. The knowledge of laser usage and application of laser was present for almost 55% of the dentist. The attitude of dentist toward the advantage of laser was less. The practice of laser dentistry was poor among dentists, and only 10% were effectively practicing laser dentistry. Conclusion: The advantages of laser in daily dental practice are more advantageous than the disadvantages such as cost of equipment and material handling. Therefore, there is a great need for creating awareness of laser dentistry. Cost-effective equipment is the need of the hour to promote laser dentistry.